Quality of Recovery and Innate Immune Homeostasis in Patients Undergoing Low-pressure Versus Standard-pressure Pneumoperitoneum During Laparoscopic Colorectal Surgery (RECOVER): A Randomized Controlled Trial. Issue 6 (13th December 2022) - Albers, Kim I.; Polat, Fatih; Helder, Leonie; Panhuizen, Ivo F.; Snoeck, Marc M.J.; Polle, S. (Bas) W.; de Vries, Hilbert; Dias, Esther M.; Slooter, Gerrit D.; de Boer, Hans D.; Diaz-Cambronero, Oscar; Mazzinari, Guido; et al.
Abstract : Objective: To study the effects of intra-abdominal pressure on the quality of recovery and innate cytokine production capacity after laparoscopic colorectal surgery within the enhanced recovery after surgery program. Background: There is increasing evidence for the safety and advantages of low-pressure pneumoperitoneum facilitated by deep neuromuscular blockade (NMB). Nonetheless, there is a weak understanding of the relationship between clinical outcomes, surgical injury, postoperative immune dysfunction, and infectious complications. Methods: Randomized controlled trial of 178 patients treated at standard-pressure pneumoperitoneum (12 mm Hg) with moderate NMB (train-of-four 1–2) or low pressure (8 mm Hg) facilitated by deep NMB (posttetanic count 1–2). The primary outcome was the quality of recovery (Quality of Recovery 40 questionnaire) on a postoperative day 1 (POD1). The primary outcome of the immune substudy (n=100) was ex vivo tumor necrosis factor α production capacity upon endotoxin stimulation on POD1. Results: Quality of Recovery 40 score on POD1 was significantly higher at 167 versus 159 [mean difference (MD): 8.3 points; 95% confidence interval (CI): 2.5, 14.1; P =0.005] and the decline in cytokine production capacity was significantly less for tumor necrosis factor α and interleukin-6 (MD: −172 pg/mL; 95% CI: −316, −27; P =0.021 and MD: −1282 pg/mL; 95% CI: −2505, −59; P =0.040, respectively) for patients operated at low pressure. Low pressure was associated with reduced surgical site hypoxia and inflammation markers and circulating damage-associated molecular patterns, with a less impaired early postoperative ex vivo cytokine production capacity. At low pressure, patients reported lower acute pain scores and developed significantly less 30-day infectious complications. Conclusions: Low intra-abdominal pressure during laparoscopic colorectal surgery is safe, improves the postoperative quality of recovery and preserves innate immune homeostasis, and forms a valuable addition to future enhanced recovery after surgery programs.